Indeks Ekologi Satwa Aves Dalam Kawasan RTH Privat Wilayah Selatan Kota Makassar - Mannan, Abdul; Zhiddiq, Sulaiman; S. Tabbu, Muhammad Ansarullah; Arfandi, Arfandi (Jurnal Environmental Science, 2024)
Urbanization and rapid development in Makassar City have led to habitat fragmentation, affecting the sustainability of avian species in the area. This study aims to understand the carrying capacity of private green spaces (RTH) in preserving avian species in Makassar City. The results indicate a moderate diversity index, with 19 bird species identified. The Eurasian Tree Sparrow and Sooty-headed Bulbul are the most common species, but species distribution is even, suggesting that no species significantly dominates. These findings indicate that despite urbanization pressures, private RTH remains an important habitat for birds. Endemic species like the Makassar White-eye, as well as threatened species such as the Java Sparrow and the Asian Koel, which are classified as Endangered and Vulnerable by the IUCN Red List, were found in the area. Additionally, these RTHs support protected species like the Great Egret, which plays a vital role in maintaining the balance of local aquatic ecosystems. The study concludes that private RTHs in southern Makassar City play a crucial role in bird conservation and the balance of urban ecosystems. Wise protection and management of these areas are essential to support biodiversity amidst intensive urbanization. These findings can serve as a basis for better environmental policy development, benefiting not only bird species but also the overall health of urban ecosystems.